Influence of Earthquake Parameters on the Bi-directional Behavior of Base Isolation Systems - Dana Abed; Jafar Al Thawabteh; Yazan Alzubi; Jamal Assbeihat; Eid Al-Sahawneh (Civil Engineering Journal, 2022)
The introduction and development of the base isolation systems, especially the friction isolator device, were done recently to improve the capacity of adaptive behavior. The efficiency of multi-phase friction pendulums comes from their complexity, which helps reduce the structural responses and enhance structures' energy dissipation under lateral loads. Nevertheless, the influence of various earthquakes' properties on the behavior of base-isolation systems subjected to bi-directional seismic loading is still unclear. Hence, further research and studies regarding the behavior and capability of these systems under bi-directional loading are still necessary before incorporating this device in real-life practical applications. Therefore, this paper is intended to investigate the bi-directional behavior of the friction isolator subjected to various ground motion records. In order to do so, different versions of the friction pendulum system are selected and compared within the study context. Generally, the study's results have shown that the behavior of the friction isolator is highly dependent on low values of the PGA/PGV ratio. Besides, pulse-like earthquakes considerably impact the response of the isolator compared to non-pulse-like ones. Doi: 10.28991/CEJ-2022-08-10-02 Full Text: PDF